Charles Perley Smith papers - Smith, Charles Perley, 1878-1948.
Correspondence, legal memoranda, printed opinions, subject files, and financial papers relating chiefly to Smith's career as a judge on the U.S. Board of Tax Appeals, later known as the U.S. Tax Court. Correspondents include William Morgan Butler, Jesse H. Jones, Robert Ramspeck, Daniel C. Roper, and David I. Walsh.
Jurist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Butler, William M. -- 1861- -- Correspondence; Jones, Jesse H. -- 1874-1956 -- Correspondence; Ramspeck, Robert, -- 1890- -- Correspondence; Roper, Daniel C. -- 1867-1943 -- Correspondence; Walsh, David I. -- 1872-1947 -- Correspondence; United States. -- Board of Tax Appeals; United States. -- Tax Court; Taxation; Jurists